The Ecology of Poverty: Nutrition, Parasites, and Vulnerability to HIV/AIDS - Stillwaggon, Eileen (International Food Policy Research Institute, 2006)
HIV/AIDS continues to spread throughout the developing world, in transition countries, and among poor and marginalized populations in industrialized countries. In its third decade, and even with increased resources, global AIDS policy is still failing to stem the epidemic. HIV prevention fails because it ignores the fundamental causes of the epidemic, it is unscientific, and it attempts to intervene at the last minute with programs limited to behavior change.